Distributional Fractal Creating Algorithm in Parallel Environment - Lan, Caihe; Fu, Weina; Deng, Huimin; Zhou, Jiantao; Liu, Shuai (International journal of distributed sensor networks, 2013)
Nowadays, the fractal is used widely everywhere. Then, its creating time becomes an important study area for complex iteration functions because the escape-time algorithm (ETA), which is the most used algorithm in fractal creating, performs not so well in this condition. In this paper, in order to solve this problem, we improve ETA into the parallel environment and reach well performance. At first, we provide a separation method of ETA to reform it into a SIMC-MC2 grid. Secondly, we prove its correctness and compute the complexity of this novel parallel algorithm. Meantime, we separate an improved ETA which we have presented into the same parallel environment and compute its complexity. Additionally, theoretical and experimental results show the characteristics of this novel algorithm. Finally, the computational result shows that a novel environment is needed to decrease large manual allocation strategies, which block the improved benefit.